Testing microservices with Mountebank - Byars, Brandon (Manning Publications, 2019)
Chapter 8. Protocols -- 8.1. How protocols work in mountebank -- 8.2. A TCP primer -- 8.3. Stubbing text-based TCP-based RPC -- 8.4. Binary support -- 8.5. Virtualizing a .NET Remoting service -- Summary -- Part 3. Closing the Loop -- Chapter 9. Mountebank and continuous delivery -- 9.1. A continuous delivery refresher -- 9.2. Creating a test pipeline -- Summary -- Chapter 10. Performance testing with mountebank -- 10.1. Why service virtualization enables performance testing -- 10.2. Defining your scenarios -- 10.3. Capturing the test data -- 10.4. Running the performance tests.